The Effect of Using Fix Up Strategy in Reading Report Text at The Grade XI of SMA Negeri 1 Sibabangun - Pohan, Doli Hairuman; Huda, Rahmat; Siagian, Abdul Rahman; Khairunnisah; Herawati Parapat, Lili; Sari, Intan Winda; Bustami Hajar, Hendra Bin; Duerawee, Abdulkarim (jurnalalfa, 2025)
The study was conducted in SMA Negeri 1 Sibabangun. The aims of this research was to find out if there a significant Effect of Using fix up strategy on Students’ report text. The writer carried out in quantitative approach by applying experimental method. The population of this research was the grade XI. They were 183 students, the writer used cluster sampling technique to get the sample. The samples were 30 students. The reading report text was applied as the instrument, the writer used “t” test formula.Based on the data analyzed, it can be found that (1 the mean scores of students result in reading report text before using fix up strategy can be said that the criteria was enough, (2) the mean scores of students result in reading report text taught by using fix up strategy can be said that the criteria was good, and (3) There was a significant effect fix up strategy in reading report text at the grade XI of SMA Negeri 1 Sibabangun. It meant that the hypothesis was accepted.